THE DECADE OF OCEAN SCIENCE: THE IMPORTANCE OF “REDISCOVERING” THE TINY AND INVISIBLE WORLD OF PLANKTON: A Década da Ciência Oceânica: a importância de “redescobrir” o minúsculo e invisível mundo do plâncton - Martins Garcia, Tatiane; Pinho Costa, Ana Cecília; Carolina Coelho Campos, Carolina; Vieira Arruda Júnior, José Pedro; de Sousa Barroso, Hortência; de Oliveira Soares, Marcelo (Arquivos de Ciências do Mar, 2022)
The Decade of Ocean Science for Sustainable Development (2021-2030) has just started, and multiple stakeholders, including scientists, policymakers, civil society, funders, and the private sector will join transnational efforts to reverse the severe cycle of ocean biodiversity decline. This viewpoint article emphasizes goal number 14 that refers to the conservation and sustainable use of marine resources, and will particularly discuss the challenges of plankton research in the ongoing Anthropocene and methods to promote a true societal understanding of these species. There are many challenges for this “tiny and invisible world”, especially because they are understudied and their importance in marine trophic webs, global biodiversity, and many plankton-mediated ecosystem services is often overlooked. This article discusses and highlights the ecological aspects of plankton communities according to the seven outcomes of the Ocean Decade. Although the impacts on benthic and nekton components (such as fish and corals) are more commonly known and recognized by society, plankton worldwide are also threatened by the loss of suitable habitats, range shift of species, organic pollution, invasive species, plastics, and global climate change (e.g., extreme floods and droughts, heat waves, and warming). Ocean literacy is currently challenged in terms of the understanding of plankton, and it is important to explain the relevance of this “invisible world” to people of all ages, cultures, and school levels. Rapid, straightforward, and appropriate communication is required to engage the public and improve awareness and science-based policies related to this important, overlooked, and threatened component of marine life. Keywords: marine plankton, marine food web, ocean decade, sustainable development, marine biodiversity.